2022
DOI: 10.3390/jmse10121928
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Relative Environmental Risk of Disinfection by Products Associated with Simple Glucose or Naturally Occurring Algal Organic Matter as Tested in Ballast Water Treatment System

Abstract: To prevent the invasion of alien species, the International Maritime Organization and the United States Costal Guard require that a ballast water management system (BWMS) be installed on ships to treat the ballast water before discharging it. BWMS technologies use active substances, which create disinfection by-products (DBPs) during ballast water treatment. This study compared the characteristics of DBPs generated in the treatment of commercial glucose with those of algal organic matter (AOM) derived from fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…THMs are formed in greater quantities compared to HAAs, which can be attributed to the structural propensity of DOM precursors to more readily bond with THMs and their more stable formation in reactions with oxidants. Studies on BWMS using AS also predominantly showed that the predominant compounds were in the order of THMs > HAAs > HANs [3,7,15,17]. The proportion of HAAs tended to increase with higher average TRO concentrations in each group (Figure S1).…”
Section: Changes In the Dbp Characteristics According To The Organic ...mentioning
confidence: 89%
See 4 more Smart Citations
“…THMs are formed in greater quantities compared to HAAs, which can be attributed to the structural propensity of DOM precursors to more readily bond with THMs and their more stable formation in reactions with oxidants. Studies on BWMS using AS also predominantly showed that the predominant compounds were in the order of THMs > HAAs > HANs [3,7,15,17]. The proportion of HAAs tended to increase with higher average TRO concentrations in each group (Figure S1).…”
Section: Changes In the Dbp Characteristics According To The Organic ...mentioning
confidence: 89%
“…The DOC concentration in ballast water may increase due to the input of new DOM because of the enhanced organic matter decomposition by the TRO, or it may decrease as a carbon source for the growth of heterotrophic bacteria. Furthermore, when the TRO is high, the growth of heterotrophic bacteria is inhibited, which means that a decrease in DOM concentration by microbial consumption is inhibited [3,31,32]. Therefore, we speculate that, in Group A, the consumption of DOC by heterotrophic bacteria was high on Day 1 because of the lower TRO concentration compared to Group B.…”
Section: Changes Of Organic Matter Concentration According To Environ...mentioning
confidence: 90%
See 3 more Smart Citations